MANAJEMEN PEMASARAN LEMBAGA AMIL ZAKAT NASIONAL: STUDI KASUS PADA BAITUL MAAL HIDAYATULLAH PUSAT JAKARTA - Nasrullah Nasrullah; Kholil Nawawi; Ikhwan Hamdani (Kasaba, 2020)
Indonesia is the largest Muslim country in the world, but also a country whose management of zakat is far behind when compared to other Islamic countries which are much smaller. Baznas stated that the potential for zakat is in the range of 217 Trillion, but which until now is managed by BAZNAS and LAZNAS is only around 8 Trillion. The wide gap between potential and achievement raises the question of how the implementation of marketing management in zakat management institutions and what causes them to not be able to maximize the existing potential. This research was conducted to find out more about marketing management within the Amil Zakat Institution specifically in Baitul Maal Hidayatullah Pusat Jakarta. The research uses field research and table research methods by collecting data in the form of interviews and institutional documents. The results of the study found that the actual programs in Baitul Maal Hidayatullah had run well, but the lack of creativity and innovation to package the program to be more attractive reduced the interest of donors / muzakki to channel more funds to the institution. The limited available staff also plays a role in the non-optimal marketing performance at the institution, too heavy a burden is placed on individuals who are in the marketing environment, making them less free to create creativity more freely. Add to this the lack of mastery of marketing science which further hinders the development of marketing in Baitul Maal Hidayatullah. Baitul Maal Hidayatullah needs to recruit more professionals so that the excessive burden borne by managers and marketing staff can be reduced and their creative potential can be maximized. And in the field additional volunteers need to provide assistance so that the benefits (funds / assistance) received can improve their standard of living.